NOxEmission Modelling and Simulation Using Point Source Dispersion Model - Dzulkafli, Nur Farhana (Universiti Teknologi PETRONAS, 2009)
Process industry is a leading industrial sectorin Malaysia and a vital part ofthe national economy. However, emissions of gases are unavoidable events during activities in process industry whichwill cause air pollution. The objective ofthis projectis mainlyto develop a computer simulation program of point source dispersion using Visual Basic software. Thepurpose of this software is to estimate the NOx concentration after the gas is released from the industrial stacks. This software is also used to estimate the percentage of people affected as a result from the exposure to NOx at certain concentration. The application is calledPoint Source DispersionSoftware(PSDS) and it is specifically developed for emission ofpollutant gases released from industrial stacks. Pasquill equation which modified by Gifford is used in this software. The model consider the atmospheric conditions, stack parameters and distance as the inputs of the simulation program. The simulation program is complex and this is the reason why the computer simulation is necessary in order to derive the reliable results. The results of PSDS show the concentration of respective pollutant gases over the distance as well as the percentage ofpeopleaffected as a result fromthe exposure to the pollutant at certain concentratioa The results from this software are validated with data from case studies and SCREEN3 (US EPA air pollution modelling software) to identify any error occur during writing the program